Cell Therapy in Ischemic Heart Disease: Interventions That Modulate Cardiac Regeneration - Maximiliano I. Schaun; Bruna Eibel; Melissa Kristocheck; Grasiele Sausen; Luana Machado; Andreia Koche; Melissa M. Markoski (Hindawi Limited, 2016)
The incidence of severe ischemic heart disease caused by coronary obstruction has progressively increased. Alternative forms of treatment have been studied in an attempt to regenerate myocardial tissue, induce angiogenesis, and improve clinical conditions. In this context, cell therapy has emerged as a promising alternative using cells with regenerative potential, focusing on the release of paracrine and autocrine factors that contribute to cell survival, angiogenesis, and tissue remodeling. Evidence of the safety, feasibility, and potential effectiveness of cell therapy has emerged from several clinical trials using different lineages of adult stem cells. The clinical benefit, however, is not yet well established. In this review, we discuss the therapeutic potential of cell therapy in terms of regenerative and angiogenic capacity after myocardial ischemia. In addition, we addressed nonpharmacological interventions that may influence this therapeutic practice, such as diet and physical training. This review brings together current data on pharmacological and nonpharmacological approaches to improve cell homing and cardiac repair.